Frailty and clinical outcomes in critically ill patients with cancer: A cohort study. Issue 8 (November 2022) - Osatnik, Javier; Matarrese, Agustín; Leone, Bruno; Cesar, Germán; Kleinert, Mercedes; Sosa, Fernando; Roberti, Javier; Ivulich, Daniel
Abstract: Introduction: Our aim was to assess impact of frailty on short-term clinical outcomes in critically ill patients with cancer. Materials and methods: We conducted a cohort study at a medical and surgical intensive care unit (ICU) in Argentina. We included 269 consecutive patients, ≥18 years old, with diagnosis of cancer. We recorded demographic and clinical characteristics, Clinical Frailty Scale (CFS, ≥5 defined a patient as frail), and the number and duration of organ support therapies during ICU stay. Primary outcome was ICU and hospital mortality. Results: Median age 69 (range 20–90); 152 (56%) patients were male. Sixty-eight (25.2%) patients presented frailty at admission. Older adults (≥65 years old) made up 62.8% of patients. Frail patients were 69.7 years versus 64.4 years for non-frail, P = 0.007, with higher Acute Physiology and Chronic Health Evaluation II (APACHE II) 14.7 ± 7 versus 10.8 ± 6, P = 0.001 and Simplified Acute Physiology Score (SAPS II) 40.1 ± 17 versus 28.7 ± 14, P = 0.001, respectively. After adjusting by age, severity score, type of admission, and type of cancer, frailty was independently associated with hospital mortality, odds ratio (OR) 4.87 (95% confidence interval [CI], 2.19–11.19, P ≤0.001). Median ICU length of stay was five days (interquartile range [IQR] 3–7) versus six days (IQR 3.8–9), in non-frail versus frail patients, respectively ( P = 0.100), and hospital stay was nine days (IQR 6–17) versus 11.5 days (IQR 7–19.5) in non-frail versus frail patients, respectively ( P = 0.085). Discussion: Frailty as a medical condition was strongly associated with worse clinical outcomes among oncologic critically ill patients.